Pelatihan Pengolahan Data Akuntansi Aset dengan Microsoft Access pada Guru - Guru di SD Negeri 2 Kalanglundo, Ngaringan, Kabupaten Grobogan - Purwati Purwati; Sumaryanto Sumaryanto; Setiyo Prihatmoko (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Effective asset data management is essential for supporting transparency and efficiency in school administration. At SD Negeri 2 Kalanglundo, located in Ngaringan Subdistrict, Grobogan Regency, asset recording is still performed manually. This traditional method makes the school prone to recording errors, data loss, and difficulties in generating accurate reports. The aim of this community service activity is to provide training for teachers on utilizing Microsoft Access as a digital tool for systematically processing asset accounting data. The training was designed to help teachers learn how to create and manage a database for school assets, thereby enhancing efficiency and accuracy in asset management. The implementation methods included lectures to explain the basic concepts of database management, demonstrations on how to use Microsoft Access, hands-on practice for building asset tables and input forms, and mentoring to guide teachers in creating automated reports for asset data. The results of the activity showed that participating teachers were able to understand the fundamental principles of using Microsoft Access, design and structure asset tables, create user-friendly input forms, and generate automated reports on school assets. This training significantly improved the teachers' information technology competencies and increased their ability to manage school assets more effectively. By adopting a digital system for asset management, the school can reduce the risk of errors and data loss, while making the asset management process more transparent and accountable. This activity is expected to have a long-term impact, encouraging the implementation of more efficient and accurate asset management practices in the school. The use of Microsoft Access as a tool for asset management will likely lead to better oversight and help the school comply with administrative standards more effectively.